Discharge delay, room for improvement? - Williams, Teresa; Leslie, Gavin; Brearley, L.; Leen, T.; O'Brien, K. (Elsevier Inc, 2010)
Aim: Patients treated in the intensive care unit (ICU) and identified as suitable for discharge to the ward should have their discharge planned and expedited to improve patient outcomes and manage resources efficiently. We examined the hypothesis that the introduction of a critical care outreach role would decrease the frequency of discharge delay from ICU. Methods: Discharge delay was compared for two 6-month periods: (1) after introduction of the outreach role in 2008 and (2) in 2000/2001 (from an earlier study). Patients were included if discharged to a ward in the study hospital. Discharge times and reason for delay were collected by Critical Care Outreach Nurses and Critical Care Nurse Specialists. Results: Of the 516 discharges in 2008 (488 patients compared to 607 in 2000/2001), 31% of the discharges were delayed from ICU more than 8 h, an increase of 6% from 2000/2001 (p <0.001). Patients in 2008 spent more in hospital from the time of their ICU admission when their discharge was delayed (p <0.001). The most common reasons for delay in 2008 were due to no bed or delay in bed availability (53%) and medical concern (24%). This is in contrast to 2000/2001 when 80% of delays were due to no bed or delay in bed availability and 9% due to medical concern. Many factors impact on patient flow and reducing ICU discharge delays requires a collaborative, multi-factorial approach which adapts to changing organisational policy on patient flow through ICU ad the hospital, not just the discharge process in ICU.